Maternal and Paternal Representations in Assisted Reproductive Technology and Spontaneous Conceiving Parents: A Longitudinal Study - Paterlini, Marcella; Andrei, Federica; Neri, Erica; Trombini, Elena; Santi, Sara; Villani, Maria Teresa; Aguzzoli, Lorenzo; Agostini, Francesca (Frontiers in Psychology, 2021)
Aim of this study was to investigate whether parental mental representations during pregnancy and after delivery differed between parents who conceived after Assisted Reproductive Treatments (ART) and spontaneous conceiving (SC) parents. Effects of specific ART variables (previous ART attempts, treatment type and cause of infertility) were also taken into account. Seventeen ART couples and 25 SC couples were recruited at Santa Maria Nuova Hospital (Reggio Emilia, Italy). At both 32 weeks of gestation (T1) and 3 months postpartum (T2) participants completed the Semantic Differential of the IRMAG, a self-report tool which measures specific domains of mental representations pertaining either individual (Child, Self, and Partner-as-parent) or parental (Self-as-parent, Own parents) characteristics. Results showed that ART parents had significantly more positive representations of the child compared to SC parents, while the scores at Partner-as-parent dimension improved from T1 to T2 for SC parents only. With regards to ART history, scores at the Self dimension were significantly less positive for ICSI than IVF parents and improved substantially from T1 to T2 only in case of mothers with previous ART attempts and of fathers at the first ART cycle. The representation of own parents increased from T1 to T2 in case of infertility diagnosis due to male factors, while a decrease emerged when infertility was due to female factors. Findings suggest the need to investigate parental mental representations after ART, in order to improve the understanding on the transition to parenthood of infertile couples and to target more specific intervention for parenting support.